2005
DOI: 10.1007/s11095-005-2505-y
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Pharmacophore-Based Discovery of Novel hPEPT1 Inhibitors

Abstract: This study demonstrates the potential of combining computational and in vitro approaches to determine the affinity of compounds for hPEPT1 and, in turn, provides insights into key molecular interactions with this transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…There is some evidence for interaction with proton-dependent active transporters: specifically, SLCO2B1 in the case of pravastatin and SLC15A1 in the case of fluvastatin. 27,28 SLCO2B1 is also implicated in hepatic uptake of pravastatin and has been examined for genetic contributions to interindividual variation in response to pravastatin. The main variant identified as having potential for pharmacogenetic response, marked by haplotype SLCO2B1*3, encodes a transporter of reduced function in vitro, but has not been associated with altered systemic drug exposure in vivo.…”
Section: Drug Transporter Proteins Affecting Statin Therapymentioning
confidence: 99%
“…There is some evidence for interaction with proton-dependent active transporters: specifically, SLCO2B1 in the case of pravastatin and SLC15A1 in the case of fluvastatin. 27,28 SLCO2B1 is also implicated in hepatic uptake of pravastatin and has been examined for genetic contributions to interindividual variation in response to pravastatin. The main variant identified as having potential for pharmacogenetic response, marked by haplotype SLCO2B1*3, encodes a transporter of reduced function in vitro, but has not been associated with altered systemic drug exposure in vivo.…”
Section: Drug Transporter Proteins Affecting Statin Therapymentioning
confidence: 99%
“…The PEPT1 pharmacophore was generated as described previously (12). The bacterial peptides were mapped onto this pharmacophore using ''Fast Fit'' algorithm and analyzed.…”
Section: Pharmacophore Mappingmentioning
confidence: 99%
“…These computational methods generally focused on diverse structures for agonists, rarely using close structural analogs (Ekins et al, 2007). Accurate predictions can be difficult due to the size and flexibility of the human PXR ligand binding domain; however, the combination of models for searching molecule databases represents a rapid way to prescreen molecules before in vitro testing, as demonstrated previously using pharmacophores for other proteins (Ekins et al, 2005a;Chang et al, 2006) as originally suggested with the first human PXR pharmacophore (Ekins and Erickson, 2002).…”
mentioning
confidence: 99%